2020
DOI: 10.3390/ma13112463
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Related Characterization of Forming-Induced Initial Damage in 16MnCrS5 Steel under a Torsional Forward-Reverse Loading Path at LCF Regime

Abstract: Forming technology and in particular cold forward rod extrusion is one of the key manufacturing technologies with regard to the production of shafts. The selection of process parameters determines the global and local material properties. This particularly implies forming-induced initial damage in representation of pores. On this background, this study aims on describing the influence of these pores in the performance of the material 16MnCrS5 (DIN 1.7139, AISI/SAE 5115) under a torsional load path in the low c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Fractographic investigations and previous studies [ 12 , 22 , 23 , 30 ] have shown that MnS inclusions also play a significant role in pore formation during the full forward rod extrusion process and in fatigue with respect to crack initiation and crack propagation. For this reason, a 3D CAD MnS model was generated from the segmented 510 Inlens images ( Figure 14 b).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Fractographic investigations and previous studies [ 12 , 22 , 23 , 30 ] have shown that MnS inclusions also play a significant role in pore formation during the full forward rod extrusion process and in fatigue with respect to crack initiation and crack propagation. For this reason, a 3D CAD MnS model was generated from the segmented 510 Inlens images ( Figure 14 b).…”
Section: Resultsmentioning
confidence: 88%
“… Diagram of fatigue specimen geometry and removal area from the component formed via full forward rod extrusion (all dimensions in mm) based on Möhring [ 22 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In tensile-compression cracking, the loads generated during forming of low-carbon steel in the longitudinal direction (rivets forming process) promote the nucleation of cracks along grain boundaries of ferrite, which in this case are initiated by the net of tertiary cementite at grain boundaries [ 32 , 33 , 34 ]. Nucleation cracks at Fe 3 C III have been shown to play a decisive role here.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the temperature effect on cubic body centered cell structures in terms of fatigue properties were also investigated [9]. Moehring et al [10] investigated the effect of forming-induced damage on LCF during torsional loading. The effect of forming-induced damage during cold extrusion regarding the axial-torsional LCF behavior has not yet been discussed.…”
Section: Introductionmentioning
confidence: 99%